THE INFLUENCE OF HUMAN RESOURCES COMPETENCE, WORK MOTIVATION, AND WORK FACILITIES ON EMPLOYEE PERFORMANCE: A LITERATURE REVIEW - Raden Hendri Ariyanto; Asri; Mirrah Samiyah (Journal of Public Health Science, 2026)
This literature review analyzes and synthesizes empirical findings regarding the influence of human resources competence, work motivation, and work facilities on employee performance across various organizational contexts. Using a systematic literature review (SLR) approach guided by PRISMA procedures, this study examines 18 empirical journal articles published between 2014 and 2024. The selected studies were obtained from reputable academic databases, including Scopus, Web of Science, Google Scholar, and ScienceDirect, using keywords such as “human resources competence,” “work motivation,” “work facilities,” “work environment,” and “employee performance.” Most of the reviewed studies employed quantitative methods, utilizing statistical techniques such as multiple linear regression, Structural Equation Modeling (SEM), and path analysis. The findings indicate that human resources competence consistently demonstrates a positive and significant influence on employee performance and emerges as the most dominant predictor across studies. Work motivation also significantly affects performance; however, its role as a mediating variable between competence and performance  shows inconsistent results depending on organizational context. Work facilities and environmental support function as enabling factors that strengthen performance, although facilities alone are insufficient without competent and motivated employees. This review underscores the importance of integrating individual capability,  psychological motivation, and organizational support systems in performance management models. The study also identifies gaps in the literature, particularly the need for more integrative and healthcare-focused research examining the simultaneous interaction of these variables. Future research is encouraged to develop comprehensive structural models and longitudinal designs to better understand performance dynamics, especially within hospital and public service organizations.